Batik Interactive Media in Learning The Fable Stories of Swan and Turtle for Tunagrahita Children - Dewanti, Ratih Artika; Wardoyo, Sugeng (Gorga : Jurnal Seni Rupa, 2025)
Interactive media in the learning and playing process is an important means to attract students interest. Providing interactive media that suits children's needs in the learning process determines success in their learning. Batik with the fable theme of the Swan and Turtle as interactive media contains a moral message, especially for mentally retarded children. The creation of this interactive media aims to complement previous studies which rarely create non-multimedia interactive media that can stimulate the sense of touch of mentally retarded children. The practical method of creating this work, the creation of Practice Based Research, practice-based research is very appropriate to use in the creation process, because in this process it produces a way in which practice can produce knowledge in research that grows in creating the work. One of the main characteristics of this research is creating and reflecting on new work through practical research carried out. The results of this creation are in the form of batik interactive media with learning fable stories of Swans and Turtles using written batik techniques in the process of realising visually appealing illustrations of fable stories, interesting interactive media not only to stimulate sensory, fine motor and train concentration, but from interactive media it also teaches manners that contain character values and preserve batik as a cultural heritage and not only as a fashion product.